2021
DOI: 10.11591/ijece.v11i5.pp4522-4530
|View full text |Cite
|
Sign up to set email alerts
|

NLP-based personal learning assistant for school education

Abstract: Computer-based knowledge and computation systems are becoming major sources of leverage for multiple industry segments. Hence, educational systems and learning processes across the world are on the cusp of a major digital transformation. This paper seeks to explore the concept of an artificial intelligence and natural language processing (NLP) based intelligent tutoring system (ITS) in the context of computer education in primary and secondary schools. One of the components of an ITS is a learning assistant, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…We used the Facebook messenger platform because a large majority of Moroccan university students uses Facebook especially with this period of pandemic that the world is experiencing in the face of Covid-19.  Natural language processing: after the chatbot receives the user request, every received message is processed through NLP, [18], [22], [23], [45].  Bot logic: the bot logical flow of interactions  Machine learning: every time the bot receives a message, it can improve its answers.…”
Section: Research Methods 21 Chatbot Frameworkmentioning
confidence: 99%
“…We used the Facebook messenger platform because a large majority of Moroccan university students uses Facebook especially with this period of pandemic that the world is experiencing in the face of Covid-19.  Natural language processing: after the chatbot receives the user request, every received message is processed through NLP, [18], [22], [23], [45].  Bot logic: the bot logical flow of interactions  Machine learning: every time the bot receives a message, it can improve its answers.…”
Section: Research Methods 21 Chatbot Frameworkmentioning
confidence: 99%
“…In 2020, Verma Shivang et al [21] mentioned about Jabberwacky's main goal that was to transition from a text-based system to a fully voice-driven system. Ann Neethu Mathew et al [22] have implemented an NLP-based personal learning assistant for school education. The chatbot proposed in this paper requires the potential to cover the whole subject's contents which can be achieved by enhancing the ontology and knowledge base.…”
Section: Literature Surveymentioning
confidence: 99%
“…Through systematic review of the literature, it was found that chatbots that are built for student's assistance are rare and do not include many features. The most recent student's assistance chatbot found in literature was an intelligent tutoring system built using NLP ontology in 2021 to assist school students in their learning journey [1]. Due to the rareness of similar chatbots, we surveyed the literature to investigate the key approaches, methodologies, and applications that can be used to build the features or the main modules of our academic assistance chatbot.…”
Section: Literature Reviewmentioning
confidence: 99%